2022
DOI: 10.1111/eje.12860
|View full text |Cite
|
Sign up to set email alerts
|

Progress and challenges in the harmonisation of European undergraduate dental education: A systematic literature review with narrative synthesis

Abstract: Progress and challenges in the harmonisation of European undergraduate dental education: a systematic literature review with narrative synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The dental education literature on this topic is dominated by proposals for curricula, unmatched by evaluative evidence of effective implementation. [17] ADEE's Pro le and Competences for Graduating European Dentist, originally published in 2005, [14] with updates in 2010 and 2017, [18,19] is a key text in efforts towards cross-national educational harmonisation and we did nd this document in use as the basis for national outcomes in Ireland and Finland, and references to its use at institutional level in Cyprus and Greece. Overall though, our ndings show that there remains considerable variation between countries and institutions in the outcomes set for dental education in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…The dental education literature on this topic is dominated by proposals for curricula, unmatched by evaluative evidence of effective implementation. [17] ADEE's Pro le and Competences for Graduating European Dentist, originally published in 2005, [14] with updates in 2010 and 2017, [18,19] is a key text in efforts towards cross-national educational harmonisation and we did nd this document in use as the basis for national outcomes in Ireland and Finland, and references to its use at institutional level in Cyprus and Greece. Overall though, our ndings show that there remains considerable variation between countries and institutions in the outcomes set for dental education in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Davda et al [ 16 ] found that some Internationally Qualified Dentists (IQDs), including from the EEA, practising in the UK recognised their different levels of experience in some clinical skills resulting from the content of their undergraduate training, negatively affected their ability to integrate into practice in the UK. Our systematic review of the literature also showed that the nature and extent of direct patient contact during training differed greatly across countries [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While for some years there has been an educational agenda to harmonise dental education across Europe, it has been shown that there is little evidence of the extent to which harmonised curricula have actually been implemented. The dental education literature on this topic is dominated by proposals for curricula, unmatched by evaluative evidence of effective implementation [ 17 ]. ADEE’s Profile and Competences for Graduating European Dentist, originally published in 2005 [ 14 ], with updates in 2010 and 2017 [ 18 , 19 ], is a key text in efforts towards cross-national educational harmonisation and we did find this document in use as the basis for national outcomes in Ireland and Finland, and references to its use at institutional level in Cyprus and Greece.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous studies to provide data on programme structures and educational practices are limited at a European level, as evidenced in two recent reviews. 10,11 Shanley et al 12 published one of the first reports on educational practices from dental schools across Europe in 1997, although it is now considered largely outdated and had a limited sample size. The CED's EU Manual of Dental Practice and the CECDO database provide data regarding the number of public and private institutions, annual intakes, course duration and percentage of female graduates.…”
Section: European Ohp Education -Current Climatementioning
confidence: 99%
“…However, these sources only include 34 EU/EEA members and the World Health Organisation's (WHO) broader definition of Europe comprises 53 countries 9 . Previous studies to provide data on programme structures and educational practices are limited at a European level, as evidenced in two recent reviews 10,11 . Shanley et al 12 .…”
Section: Introductionmentioning
confidence: 99%